PERAN BAHASA INDONESIA DI OBJEK WISATA DESA PEMATANG SERAI KABUPATEN LANGKAT - kamal, Mustafa (Tourism, Hospitality And Culture Insights Journal, 2025)
This research aims to identify and analyze the potential of local culture as a tourist attraction in Pematang Serai Village, Lalat Regency. This village has a rich culture in the form of traditional arts, customs, and local culinary that reflect the identity of the local community. A qualitative approach was used in this study through field observation and interviews. The results of the study show that the local cultural potential of this village strongly supports the development of community-based tourism, especially with the existence of river tourism and culinary attractions. However, tourism development still faces challenges such as lack of infrastructure, limited promotion, and low public awareness of the economic value of the tourism sector. Empowerment efforts through tourism village programs and increasing community participation are the main keys in creating sustainable and competitive tourist destinations. This research recommends improving infrastructure, community education, and active promotion to strengthen the position of Pematang Serai Village as a cultural-based tourist destination.